Les structures d’encadrement du tourisme en Tunisie au cours de la période coloniale (1881-1956) - Lassaad Dandani (Études Caribéennes, 2024)
This article proposes to retrace the route of the structural organization of the tourist activity in Tunisia during the period of the French Protectorate. Our initial hypothesis is that there is no tourism without official involvement of the administration of the Protectorate. That is to say, without a policy of supervision, without an administrative framework of management, without legislation, without the initiative of physical and moral actors. We will therefore try to understand the nature of the different structures set up by the administration of the Protectorate to manage the tourist activity. Indeed, this intervention was either in a direct way through specialized services or by specific organizations. In any case, the diversity of the supervision structures reveals the importance of tourism under the French Protectorate as a major economic and cultural activity. It constituted a testimony on the involvement of the administration of the Protectorate in the promotion of tourism.